Readiness and Acceptance of Health Providers using Clinical Decision Support System at Probolinggo Primary Healthcare Centers - Riza Alfian; Yunita Nita; Hanni Prihhastuti Puspitasari; Rokayah Rokayah (Journal of Public Health and Pharmacy, 2025)
Introduction: The government targets a significant reduction in antibiotic resistance by 2030 through wise antibiotic management, including implementing the Clinical Decision Support System (CDSS) for Health Providers in Non-Pneumonia acute respiratory infections (ISPA) and Non-specific Diarrhea in Primary Healthcare Centre (Puskesmas). However, the readiness and acceptance of Health Providers to CDSS need to be evaluated. This study evaluates the readiness and acceptance of doctors, nurses, midwives, pharmacists, and pharmacists' assistants in Puskesmas using CDSS. Methods: The method used was a cross-sectional quantitative survey with snowball sampling of 185 respondents at the Probolinggo Puskesmas in July-August 2024. The questionnaire was developed based on a combination of the Technology Readiness Index and the Technology Acceptance Model (TRAM), and the data was analyzed using SEM-PLS (Structural Equation Modeling-Partial Least Squares). Result: This study revealed that optimism contributed positively to the perception of ease of use (PEOU) and perception of benefits (PU) of CDSS. Innovation also contributed positively to PEOU, but not significantly to PU. Optimism increases PEOU and PU, while innovation only increases PEOU. Although innovation is insignificant to PU, it has a more significant impact on PEOU than optimism. Conclusion: These findings also show that PU affects the attitude of Health Providers to use CDSS (? = 0.286, p < 0.001) but does not directly affect behavioral intentions (? = 0.081, p = 0.250). PEOU significantly affected PU (? = 0.617, p < 0.001) and attitude (? = 0.661, p < 0.001). Attitudes towards CDSS greatly influenced the behavioral intentions of healthcare providers to use it (? = 0.851, p < 0.001), making it a strong predictor of CDSS adoption. The integration of TRI and TAM in predicting the readiness of Health Providers has proven helpful in understanding the factors of CDSS adoption in Puskesmas. These findings highlight the importance of training for health providers to improve CDSS readiness and acceptance. In addition, the results of this study can be the basis for policy development in implementing CDSS Primary Healthcare Centers to support a more rational use of antibiotics.